2023
DOI: 10.1021/acs.chemrev.2c00608
|View full text |Cite
|
Sign up to set email alerts
|

A New Phase of Networking: The Molecular Composition and Regulatory Dynamics of Mammalian Stress Granules

Abstract: Stress granules (SGs) are cytosolic biomolecular condensates that form in response to cellular stress. Weak, multivalent interactions between their protein and RNA constituents drive their rapid, dynamic assembly through phase separation coupled to percolation. Though a consensus model of SG function has yet to be determined, their perceived implication in cytoprotective processes ( e.g. , antiviral responses and inhibition of apoptosis) and possible role in the pathogenesis of various neurodegenerative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 259 publications
(565 reference statements)
0
32
0
Order By: Relevance
“…[116] Copyright 2020, Elsevier B.V. sample-to-answer time of <15 min, indicating its great promise for POC diagnosis applications. [121,204]…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…[116] Copyright 2020, Elsevier B.V. sample-to-answer time of <15 min, indicating its great promise for POC diagnosis applications. [121,204]…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…[98,[203][204][205] Among these diseases, AD is a widely investigated neurodegenerative disease that accounts for 70% of all dementia and affects the quality of human life. [203][204][205] Early diagnosis of AD is of vital importance because there is no certain treatment after the lesion has progressed in the late stage. [116,203] In 2020, Park et al demonstrated a dualantibody-modified GFET biosensor for multiplex detection of two AD biomarkers (Figure 11a).…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The current studies reveal a likely interaction between native C9orf72 protein and PRMTs in regulating these pathways in C9orf72-mutation-mediated neurodegeneration. Recent studies have highlighted the importance of stress granule formation and requisite liquid-liquid phase separation as modulators of C9orf72 mutation-mediated cytotoxicity in cell-based models ( Liu et al, 2023 ; Millar et al, 2023 ). For example, C9orf72 has been demonstrated to be a regulator of the integrated stress response (ISR), facilitating stimulation of the unfolded protein response (UPR), inhibition of stress granule formation, and LLPS through interaction with eIF2a ( Zheng et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stress granule (SG) proteome was obtained from RNAGranuleDB [55] by taking only Tier 1 SG proteins. The nucleolar proteome was derived from [56], by only accepting proteins with "Enhanced" or "Supported" nucleolar localization to gain a high-confidence dataset.…”
Section: Data Collection For Bioinformatics Analysismentioning
confidence: 99%